9+3x-1=9x+17-7

Simple and best practice solution for 9+3x-1=9x+17-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+3x-1=9x+17-7 equation:


Simplifying
9 + 3x + -1 = 9x + 17 + -7

Reorder the terms:
9 + -1 + 3x = 9x + 17 + -7

Combine like terms: 9 + -1 = 8
8 + 3x = 9x + 17 + -7

Reorder the terms:
8 + 3x = 17 + -7 + 9x

Combine like terms: 17 + -7 = 10
8 + 3x = 10 + 9x

Solving
8 + 3x = 10 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
8 + 3x + -9x = 10 + 9x + -9x

Combine like terms: 3x + -9x = -6x
8 + -6x = 10 + 9x + -9x

Combine like terms: 9x + -9x = 0
8 + -6x = 10 + 0
8 + -6x = 10

Add '-8' to each side of the equation.
8 + -8 + -6x = 10 + -8

Combine like terms: 8 + -8 = 0
0 + -6x = 10 + -8
-6x = 10 + -8

Combine like terms: 10 + -8 = 2
-6x = 2

Divide each side by '-6'.
x = -0.3333333333

Simplifying
x = -0.3333333333

See similar equations:

| (x)=-16t^2+96t | | 2d-d=20 | | 0.2(k+2.4)=3.2k | | 5+2n=12n+15 | | -5-4x=7-6x | | 19=25+4x | | 6a-8=-2 | | -x+5=37 | | -9+x=-x+5 | | y-2+y=2 | | 10s-4s=12 | | 4.5-3.54x=8.04 | | 3x^2-15x=2 | | -2z=26 | | 2x+3=7x-22 | | 3x^3y^4*5x^2y= | | 5y-3y=18 | | -29-3x=10-6x | | 0.6+8=1.4 | | 37=-x+5 | | C=37.51+0.25x | | 2a-4=4 | | 6p+5=-4-(1-4p) | | 17d+3d=20 | | -3n-7+5n=-6+2n-1 | | 0=12x^2-60x+50 | | 7x-3(4w+8)=11 | | x-21+2x=-5-2x-9 | | 47=6n-5+n | | 2p^2q^2+8pq-24=0 | | -24+3x=18-4x | | 16m-10m=6 |

Equations solver categories